Pengembangan Metoda Boucherie untuk Pengawetan Bambu. - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Kehutanan UGM, 1999)
ABSTRAK Since the natural durability of cut bamboo culm is generally low in the tropical environment, it is necessary to protect and preserve it from decay and insect attact. Boucherie method for wood preservation has been modified by Liese so that the method becomes suitable for bamboo preservation. The preservative liquid is penetrated into one end of the culm through plastic hoses connected to an electric pump. The liquid pressure is about 2 kg/cm2. The modified method has been successfully adopted by Environmental Bamboo Foundation. However the process should be done immediately after the cubn has been cut off. In addition, it is not recommended to start the process more than 12 hours after the culm has been cut off: Accordingly the process needs to be done close to the rural area where bamboos are cultivated, but on the other hand problem arises due to the lack of the electric availability in the rural area. Research has been conducted experimentally to obtain more suitable bamboo preservation method. Boucherie method has been further modified, the electric pump has been substituted with pressurised tank. Pressure of the air can be raised by pumping the tank manually. A bamboo preservation system has been developed in this research. The system obtained meets the following requirements, i.e: no electricity needed, the noise and the process time are reduced, and the bamboo can be treated within 10 days after the culm has been cut off.